Pengaruh Jumlah Taksiran dan Piutang Terhadap Laba Bersih PT Pegadaian (Persero) UPC Campalagian Periode 2016-2018 - Wulan Ayuandiani; Ayub Hardianto; Nurfitriayu Mandasari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This study aims to determine the effect of the number of estimates and accounts receivable partially to net income and to determine the effect of the number of estimates and account receivable simultaneously on net income PT. Pegadaian (Persero) UPC Campalagian period 2016-2018. This study uses classical assumption test techniques, multiple linear regression, coefficient of determination, F test and t test. The population sampled are financial statement, reports on the number of estimates and accounts receivable period 2016-2018. Data collection with documentation techniques. The calculation result obtained by the value of tcount the estimates amount of -0,281 with a significant level of 0,781 and accounts receivable of 4,173 with a significant level of 0,000, while the value of ttable is 2,03452. This shows that the estimates amount partially has a negative and insignificant effect on net income (-0,281 < -2,03452 dan 0,781 > 0,05), while accounts receivable have a positive and significant effect on net income (4,173 > 2,03452 dan 0,000 < 0,05). The value of Fcount the number of estimates and receivable obtained is 17,066 with a significant level of 0,000, while the value of Ftable is 3,28. This shows that the number of estimates and account receivable simultaneously has a positive and significant effect on net income (17,066 > 3,28 dan 0,000 < 0,05)